Recognizing New Types of Stacking Interactions by Analyzing Data in the Cambridge Structural Database - Dušan P. Malenov; Snežana D. Zarić (Chemistry, 2023)
Cambridge Structural Database (CSD) is the largest repository of crystal data, containing over 1.2 million crystal structures of organic, metal–organic and organometallic compounds. It is a powerful research tool in many areas, including the extensive studying of noncovalent interactions. In this review, we show how a thorough analysis of CSD crystal data resulted in recognition of novel types of stacking interactions. Even though stacking interactions were traditionally related to aromatic systems, a number of crystallographic studies have shown that nonaromatic metal–chelate rings, as well as hydrogen-bridged rings, can also form stacking interactions. Joined efforts of a CSD analysis and quantum chemical calculations showed that these new stacking interactions are stronger than stacking interactions of aromatic species and recognized them as very important attractive forces in numerous supramolecular systems.